Penggunaan Media Gambar untuk Meningkatkan Kreativitas Siswa dalam Menggambarkan Motif Batik pada Kelas VII-3 SMP Negeri 1 Cariu Kabupaten Bogor - Heldajani (Institut Agama Islam Sahid (INAIS) Bogor, 2020)
This research is motivated by the not yet optimal ability of students in drawing batik motifs because batik learning is currently still theoretical. Therefore, the use of image media is expected to improve students' ability to draw batik motifs through imitating and modifying activities. The method used in this research is Classroom Action Research which is carried out in three cycles. The location of the research was carried out at SMP Negeri 1 Cariu, Bogor Regency, for students in class Vlll-3. The data collection techniques used were tests, observations, questionnaires, interviews, literature studies, field notes, and documentation studies. In analyzing research data, data obtained from test activities and observations from learning activities were analyzed descriptively and percentages. The findings of the research are: a) Planning for learning to draw batik motifs is carried out through the stages: reviewing SK and KD, compiling PP repairs, developing drawing media, and developing research instruments. Planning activities take into account the curriculum and student needs. b) The implementation of learning to draw batik motifs using image media can increase student activity, increase students' insight into the art of batik craft, and can imitate and modify batik motifs. The learning stages include: concept exposure, imitating activities and modifying activities. c) The results obtained from learning to draw batik motifs using image media based on tests given to students showed an increase with an average test score of 70.00 (cycle 1) to 76.58 (cycle 2) and 77.22 (cycle 1). 3). Based on these data, it can be concluded that the use of image media can improve students' ability to draw batik motifs through imitating and modifying batik motifs.